Ontogenetic Shifts in the Number of Axons in the Olfactory Tract and Optic Nerve in Two Species of Deep-Sea Grenadier Fish (Gadiformes: Macrouridae: Coryphaenoides) - Lisney, Thomas J.; Wagner, Hans-Joachim; Collin, Shaun P. (Frontiers in Ecology and Evolution, 2018)
Neuroanatomical studies of the peripheral sense organs and brains of deep-sea fishes are particularly useful for predicting their sensory capabilities and ultimately their behaviour. Over the abyssal plane (between 2,000 and 6,000 m), communities of grenadiers (Gadiformes: Macrouridae) play an important ecological role as predator-scavengers. Previous studies suggest that these fishes rely heavily on chemosensation, especially olfaction. Furthermore, at least one species, Coryphaenoides armatus, undergoes an ontogenetic shift in the relative size of the optic tectum and the olfactory bulbs, suggesting. a shift from a reliance on vision to olfaction during ontogeny, apparently in association with a shift to a more scavenging lifestyle. Here, we compared the olfactory and visual sensory inputs to the brain in C. armatus, and in a second, closely-related species, Coryphaenoides profundicolus, by assessing the total number of axons (myelinated and unmyelinated) in the olfactory tract and optic nerve in a range of individuals from both species. In C. armatus, the numbers of axons in both tract and nerve increased with body size, with the total number of axons in the olfactory tract being far greater than the number of axons in the optic nerve. These differences became more pronounced in larger animals. In the two smaller C. profundicolus individuals (≤315 mm SL), there were more axons in the optic nerve than in the olfactory tract, but the opposite situation was found in larger individuals. As in C. armatus, the number of olfactory tract axons also increased with body size in C. profundicolus, but in contrast, the number of optic nerve axons decreased in this species. These results suggest that both C. armatus and C. profundicolus undergo an ontogenetic shift in sensory orientation, with olfaction becoming relatively more important than vision in larger animals. The differences in the ratio of olfactory tract to optic nerve axons in C. armatus indicate that olfaction is of particular importance to larger individuals of this species. In both species, the percentage of myelinated axons in the olfactory tract was relatively low, but we found evidence for interspecific and ontogenetic variation in the percentages of myelinated axons in the optic nerve.